Hubungan Motivasi Mahasiswa dan Komunikasi Interpersonal dalam Peningkatan Prestasi - Magvira Yuliani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
Motivation is one of the factors that can affect student academic achievement, it is an indicator of the quality and quantity of knowledge that has been mastered by students. The outcomes are influenced by several factors including the interpersonal communication of lecturers and the motivation possessed by students in studying. This study aims to determine the relationship between students’ motivation in the Faculty of Communication, University of Muhammadiyah, Prof. Dr. Hamka, and interpersonal communication in the learning process in class. The research method uses quantitative research using a questionnaire and descriptively analyzed using David McClelland's needs theory approach as the basis of the research. Research shows that interpersonal communication influences students’ learning processes, especially for students with affiliation motivation. Thus, by knowing students’ motivation during the learning process, lecturers can choose and use the appropriate type of communication so that optimization in the teaching and learning process can be achieved.